Case report: Application of color Doppler sonography for the assessment of pulmonary consolidations in a dog - Kraszewska, Katarzyna; Gajewski, Michał; Boysen, Søren R. (Frontiers in Veterinary Science, 2023)
A 1,5-year-old male maltipoo presented to the emergency service for dyspnea, weakness, and cough. Echocardiographic examination showed evidence of pulmonary hypertension with a McConnell sign.Lung ultrasound, including color doppler, was performed and identified two distinct populations of lung consolidation. Color doppler analysis of the first type of consolidation showed absence of blood flow within regions of the consolidation, and a congested thromboembolic vessel with flow amputation. These findings were consistent with the "vascular sign" reported in human medicine and prompted consideration of pulmonary thromboembolism as a differential diagnosis. In the second type of consolidation color doppler identified blood flow within the pulmonary vessels of the consolidated lung, forming a "branching tree-like" pattern that followed the anatomical course of the pulmonary vasculature. These findings suggested blood flow was preserved within the pulmonary vasculature of the consolidated lung and prompted consideration of inflammatory causes of pulmonary pathology. On recheck 6 days later, recanalization of the first type of consolidation was identified with color doppler. The case was followed serially once a month for 5 months with LUS, which showed continued improvement. Based on a positive fecal Baermann test, a final diagnosis of Angiostrongylus vasorum was made. New or Unique information Provided -This is the first report of color doppler LUS being used to characterize and help differentiate the cause of lung consolidation in dogs.In human medicine, color doppler analysis is one component of LUS that can help differentiate thromboembolic from inflammatory pulmonary lesions (1,2,3,4). Absence of blood flow within regions of lung consolidation and the so-called "vascular sign" are consistent with thromboembolic pulmonary disease and is believed to result from the occlusion of a vessel by embolic material (4). By contrast, the identification of blood flow and a "tree-like" vascular pattern within regions of lung consolidation are more consistent with inflammatory causes of pulmonary disease (2,4,5,6). Pulmonary thromboembolism (PTE) is challenging to diagnose